The corruption of play : mapping the ideological play-space of AAA videogames - McMahon, Christopher (Emerald Publishing Limited, 2022)
AAA videogames often offer expansive experiences to the millions who engage with the medium, but they are vulnerable to disruption from neoliberal structures. The Corruption of Play explores how neoliberal ideology corrupts play in AAA videogames by creating conditions in which play becomes unbound from leisure, allowing play to be understood, undertaken, and assessed in economic terms, and fundamentally undermining the nature of play. Providing a cutting-edge and innovative approach to this problem, McMahon uses cognitive mapping to make neoliberalism visible in play-space, showcasing a new way of seeing and understanding how play is enabled and how the player forms an understanding of themselves by it. How does the player form their sense of self in the videogame? What level of agency does the player have? How are AAA videogames consumed and what is the extent of the corruption of play? Offering a timely level-up to the existing critical work on videogames, McMahon's revelations that play in AAA videogames does not often occur under ideal conditions due to the influence of neoliberal ideology are a captivating read for communication and media scholars interested in videogames. Understanding that play should be a core activity, and a natural barrier to market and economic logics, McMahon sets the scene for equipping us to understand how the process of neo liberalisation can be resisted.